Compact System for Colorimetric Sensor Arrays Characterization Based on Computer Screen Photo-Assisted Technology - Giovanni Gugliandolo (MDPI AG, 2021)
The detection of the spectral fingerprint of chemical sensors through the combined use of an LCD and a webcam is an alternative approach for chemical sensor characterization. This technique allows the development of more compact, cheap, and user-friendly measurement systems compared to the more classic instruments, such as spectrometers and gas chromatography systems. In the Computer Screen Photo-assisted Technique (CSPT), a display acts as a light source, and a conventional camera (e.g., a webcam) plays the role of a detector. The light from the LCD is reflected (or transmitted) by the chemical sensor, and the camera detects it. In the present contribution, we propose a compact and low-cost platform based on CSPT for the characterization of colorimetric sensor arrays. The system can provide spectral information of both reflected and transmitted light from the sample. Further, a 2.4-inch LCD and three different detector’s (a webcam, an RGB sensor, and a camera module) performances have been evaluated and discussed. The developed system includes a UDOO-based single board computer that makes it a stand-alone measurement system.